Analysis Of Nullification And Cancellation Of Notary Deed In The Perspective Of Act No. 2 Of 2014 On Notary - Devi Nindy Lestari; Lathifah Hanim (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
The purpose of this study was to: 1) to assess and analyze the implementation of nullification and cancellation Deed in the perspective of Act No. 2 of 2014 concerning Notary, 2) to assess the implications of the law, and 3) to identify and analyze the barriers and solutions regarding nullification and cancellation of the Deed. The data used in this study are primary data, secondary data, and data that can uphold tertiary study, which was then analyzed by descriptive analytic method.Based on the results of data analysis can be concluded that: 1) notarial deed nullification and cancellation can occur for non-fulfillment of objective conditions; terpenuhiya not subjective terms of a contract, and can be canceled by the parties themselves. 2) The legal implications as a result of nullification and cancellation Deed is a notarial deed which can be canceled by the parties themselves, the notarial deed null and void, the notarial deed only has the strength of evidence deed under hand. 3) Obstacles and solutions that not all Notaries know and understand the terms of authenticity, validity and causes nullification and cancellation of a notarial deed. Notaries who do not understand the need to study the causes nullification and cancellation deed refers mainly to provisions UUJN and the Civil Code.Keywords: Deed; Nullification and Cancellation.